“Creation is Incarnation”: Similarity and Difference in Hans Urs von Balthasar's Christology and Theology of Theosis - Lett, Jacob (Pro ecclesia, 2024)
I analyze how “creation is incarnation” in alternative readings of Maximus, particularly focusing on differing visions of how similarity/identity and dissimilarity/difference function in Christology and theosis. I consider Jordan Daniel Wood's diagnosis of Maximus interpretations and his alternative reading of Maximus in order to set-up an in-depth reading of Hans Urs von Balthasar. Balthasar's account of similarity and difference is richly textured, including key components of his trinitarian theology, Christology, and theosis. I draw these components into one place and show how Maximus and other theologians whom Balthasar engages influence his Christo-logic of similarity and difference. At minimum, this account casts doubt on the assertion that the analogia entis is an independent principle that Balthasar justifies in his Christology. More positively, I argue that Balthasar offers a theology of creaturely divinization that layers hypostatic, ousianic, and trinitarian logic and that building blocks in Balthasar's account are inspired by Maximus's Christology.